"Nation against the system": nationalist rap as the voice of marginalized classes and losers from the neoliberal transformation in Poland. Issue 4 (2nd October 2021) - Żuk, Piotr; Żuk, Paweł
ABSTRACT: This article analyzes the phenomenon of nationalist rap in Poland. According to the authors, the seemingly independent rap uses a more radical version of the discourse of the right-wing establishment that refers to nationalism, Islamophobia, and opposition to migrants. As there is no left-wing cultural narrative in the public space, nationalist rap has become a voice of those who have not benefited from the process of neoliberal transformation in Eastern Europe and a musical setting for the far right. From this perspective, nationalist rap is an identity response to class marginalization.